Production and Utilization of Keratin and Sericin-Based Electro-Spun Nanofibers: A Comprehensive Review - S. Mowafi; H. El-Sayed (Journal of Natural Fibers, 2023)
This article review is devoted to throw the light on the unique characteristics of keratin- and sericin-based electro-spun nanofibers which make them suitable for various applications in different fields. The principles of electro-spinning together with the various devices usually used to fabricate nanofibers are also highlighted. The chemistry of keratin and sericin bio-polymers and the methods of extraction from their respective natural resources, such as wool and natural silk fibers, were criticized. Blending of keratin or sericin with various natural and synthetic polymeric materials to improve their rheological properties to obtain electro-spinnable composite suitable for production of functional nano-fibrous mat was discussed. Incorporation of nanosized metals and metal oxides as well as bioactive materials into keratin and sericin-based electro-spun nanofibers imparts new functions to the produced nanofibres. The utilization of these functional nano-fibrous mats in biomedical, filtration and smart textile applications was illustrated. The current status and future prospects of the electro-spun nanofibers were highlighted.